Site and severity of coronary narrowing and infarct size in man. Issue 3 (September 1980) - Hori, M; Inoue, M; Ohgitani, N; Tsujioka, K; Abe, H; Fukui, S; Minamino, T
Abstract : The relation between the site and severity of coronary artery lesion and infarct size was investigated in 59 patients with acute myocardial infarction. All patients had no prior myocardial infarction and had at least one significant coronary narrowing (greater than or equal to 75%) in one of the major coronary arteries or in the first diagonal branch. Left ventriculography and selective coronary arteriography were performed on average 2.2 months after the onset of infarction to identify the site and severity of coronary narrowing and to assess the extent of the non-contracting segment (akinetic, dyskinetic, or aneurysmal). Thirty-four of 59 patients were studied enzymatically and total CK released was taken as an indication of infarct size. Non-contracting segment and total CK released in group L-I (narrowing proximal to the first diagonal branch) were significantly larger than those in group L-II (a coronary lesion distal to the branch). The data also indicate that the perfusion area of the first diagonal branch is as large as that of the left anterior descending artery below the first diagonal branch. In contrast to left anterior descending artery disease, the involvement of the right ventricular branch did not significantly influence the infarct size. However, infarct size was significantly larger in eight patients with the left ventricular branch of the right coronary artery supplying the predominantly large area of posterior wall of the left ventricle than in nine patients with small left ventricular branches. It was also shown that the severity of coronary narrowing does not correlate with the infarct size in either left anterior descending or right coronary artery disease.